Rancang Bangun Mesin Pemeras Tebu 3 Roll dengan Penyajian Otomatis - Jajang Jaenudin; Septika Ambarwati; Hendriko; Nur Khamdi (Jurnal Elektro dan Mesin Terapan, 2022)
Sugarcane juice can be taken by squeezing sugarcane stalks using a squeeze machine. The existing squeezing machines are still not efficient and relatively low production speed. The main factor of machine performances was on rolls quantity and its arragement. To overcome this problem, we have designed and fabricated the machine with 3-rolls by optimally speed and inter-rolls distance setting. The squeezer rolls were driven by 1-phase motor with fixed speed by the gear ratio setting. The distance and position between the rolls are arranged in such a way that the pressing power is maximized, but it is maintained to avoid stuck. The peeled and cut sugarcane is loaded into the hopper. Then, the sugar cane is drawned and squeezed by rolls. After that, it filtered and stored in the container. This machine is equipped with an automatic system for dispensing sugarcane juice from the container to the glass. The results show that the efficiency of this machine is around 65.1% with 78.1 ml/s production speed. Sugarcane juice produced is relatively clean without contaminated by it dregs